Complex life cycle, broad host range and adaptation strategy of the intranuclear Paramecium symbiont Preeria caryophila comb. nov. Issue 7 (26th April 2018) - Potekhin, Alexey; Schweikert, Michael; Nekrasova, Irina; Vitali, Valerio; Schwarzer, Sabine; Anikina, Arina; Kaltz, Oliver; Petroni, Giulio; Schrallhammer, Martina
Abstract: Holospora and related bacteria are a group of obligate Paramecium symbionts. Characteristic features are their infectivity, the presence of two distinct morphotypes, and usually a strict specialization for a single Paramecium species as host and for a nuclear compartment (either somatic or generative nucleus) for reproduction. Holospora caryophila steps out of line, naturally occurring in Paramecium biaurelia and Paramecium caudatum . This study addresses the phylogenetic relationship among H. caryophila and other Holospora species based on 16S rRNA gene sequence comparison analyzing the type strain and seven new macronuclear symbionts. Key aspects of Holospora physiology such as infectivity, symbiosis establishment and host range were determined by comprehensive infection assays. Detailed morphological investigations and sequence-based phylogeny confirmed a high similarity between the type strain of H. caryophila and the novel strains. Surprisingly, they are only distantly related to other Holospora species suggesting that they belong to a new genus within the family Holosporaceae, here described as Preeria caryophila comb. nov. Adding to this phylogenetic distance, we also observed a much broader host range, comprising at least eleven Paramecium species. As these potential host species exhibit substantial differences in frequency of sexual processes, P. caryophila demonstrates which adaptations are crucial for macronuclear symbionts facing regular destruction of their habitat. Abstract : New insights in the complex biology of a group of macronuclear-specific bacterial symbionts reveal their advanced adaptation to a broad range of host species and their surprisingly large phylogenetic distance to Holospora species, to which they originally have been assigned.